Sanksi Pidana terhadap Anak yang Melakukan Tindak Pidana Aborsi - Ni Luh Putu Hinduswari; A A Sagung Laksmi Dewi; Ni Made Sukariyati Karma (Jurnal Interpretasi Hukum, 2020)
Abortion is a health problem for the community, especially women because it has an impact on maternal death or the end of pregnancy with a fetus removed from the womb. The main cause of death of pregnant women and childbirth is bleeding and infection. Every human wants the law to be enforced to be more effective not only in the form of order. One example of the cases is in Court Decision Number 5 / Pid.Sus-Anak/2018/PN.Mbnd and legal protection for children that must be upheld. The formulation of the problem raised were how criminal sanctions against children who commit abortion and how legal protection for children who commit abortion is. This study used normative legal research that is in the study of systematically processing library materials. This research was conducted using secondary data obtained from primary material by analyzing the laws and regulations relating to the title of this journal.Thus, conclusions can be drawn that criminal sanctions against children who commit criminal acts of abortion are regulated in the Criminal Code, and Court Decision Number 5 / Pid.Sus-Anak / 2018 / PN.Mbn imposed Criminal Sanction namely imprisonment for 6 (six) months and work training for 3 (three) months against the defendant in accordance with the provisions of article 77 A paragraph (1) jo, and legal protection is regulated in Law No. 36 of 2009 concerning Health. In addition, there must be efforts from the government and the community and parents to prevent the occurrence of cases of abortion among teenagers.